2022
DOI: 10.1002/cnr2.1675
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for cancer‐specific survival in 220 patients with breast cancer: A single center experience

Abstract: Objectives Hospital‐based breast cancer survival studies are scarce in western Iran. Furthermore, the relationship between breast cancer survival and clinical parameters has been extensively studied, but many of the findings come from developing countries. This paper aims to estimate the survival of hospital‐based breast cancer patients and its predictor factors. Method This retrospective analysis was conducted on 578 patients with primary breast cancer who underwent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Earlier studies in Iran have estimated that the prevalence of breast cancer was 120 per 100,000 among adult women [ 4 ]. It accounts for more than 20% of all cancers in Iran [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in Iran have estimated that the prevalence of breast cancer was 120 per 100,000 among adult women [ 4 ]. It accounts for more than 20% of all cancers in Iran [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors include age, hormone receptors, histological subtype, molecular subgroup, grade, perineural invasion (PNI) status, lymphovascular invasion (LVI) status, Ki-67 percentage, lymph node metastasis, distant metastasis, tumor size, stage, and treatments applied to the patient. [5][6][7] We know that prognostic factors and gene assay are effect the treathment of the breast cancer. In addition, studies on gene assay have shown that in older and younger patients different genes have prognostic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…According to the estimates provided by the World Health Organization (WHO), breast cancer accounted for approximately one in six global fatalities. In 2018, there were approximately two million new breast cancer cases, making it the most prevalent cancer among women and the second most prevalent cancer globally, following lung cancer (9).…”
Section: Introductionmentioning
confidence: 99%